Investigation of RFLP Haplotypes β- Globin Gene Cluster in Beta-Thalassemia Patients in Central Iran - Zahra Sajadpoor; Zeinab Amini-Farsani; Majid Motovali-Bashi; Mitra Yadollahi; Farrokh Yadollahi (International Journal of Hematology-Oncology and Stem Cell Research, 2019)
Background: Beta-thalassemia is one of the most prevalent inherited blood diseases among Iranians. The aim of this study was to elucidate the chromosomal background of beta-thalassemia mutations in Esfahan province, Iran. Materials and Methods: In this study, we investigated three frequent mutations (c.315+1G>A, c.93-21G>A and c.92+5G>C in the β-globin gene, the frequency of RFLP haplotypes, and LD between markers at β-globin gene cluster) in 150 beta-thalassemia patients and 50 healthy individuals. The molecular and population genetic investigations were performed on RFLP markers HindIII in the c.315+1G>A of Gγ (HindIIIG) and Aγ (HindIIIA) genes, AvaII in the c.315+1G>A of β-globin gene and BamHI 3' to the β-globin gene. All statistical analyses were performed using Power Marker software and SISA server. Results: Fifty percent of beta-thalassemia patients were associated with these mutations. Haplotype I was the most prevalent haplotype among beta-thalassemia patients (39.33%) and normal individuals (46%). The commonest c.315+1G>A mutation in our population was tightly linked with haplotype III (43.75%) and haplotype I (31.25%). The second prevalent mutation, c.92+5G>C, was 90%, 6.66%, and 3.33% in linkage disequilibrium with haplotypes I, VII, and III, respectively. The c.93-21G>A mutation indicated a strong association with haplotype I (80%). Conclusion: Our study participants like beta-thalassemia patients from Kermanshah province was found to possess similar haplotype background for common mutations.The emergence of most prevalent mutations on chromosomes with different haplotypes can be explained by gene conversion and recombination. High linkage of a mutation with specific haplotype is consistent with the hypothesis that chromosomes carrying beta-thalassemia mutations experienced positive selection pressure, probably because of the protection against malaria experienced by beta-thalassemia carriers.